Аntithrombotic prophylaxis and therapy in oncology - Z. S. Barkagan; A. N. Shilova; S. A. Khodorenko (Бюллетень сибирской медицины, 2003)
In the article the authors revise a number of methods used in clinic for the description of hypercoagulation syndrome and consider that persistent trombinemia signs and signs of platelet hyperaggregation with the increased consumption of them are the most reliable markers of hypercoagulation and prethrombosis state. Methodology of oncothrombosis prophylaxis and therapy is discussed. Authors demonstrate that heparin therapy decreases the risk of development of spontaneous and postsurgery thrombosis as well as of DIC-syndrome in cancer patients. Authors define the ways of further optimization of thrombotic complications prophylaxis and therapy using thrombine inhibitors and the study of their effects on oncogenesis.